Potensi Jenis Kupu-Kupu sebagai Bioindikator Kondisi Lingkungan Kawasan Perkotaan - Siva Devi Azahra (Gunung Djati Conference Series, 2021)
Urban areas experience various symptoms of environmental decline caused by rapid development in industry and settlements and increased transportation activities. These cause a decrease in green space and changes in habitat-forming ecological components that can affect the biotic community in the habitat. Butterflies are insects with a widespread and can reflect the environmental conditions that become their habitat. This study examines the potential of various types of butterflies as bioindicators of environmental conditions by analyzing the relationship between butterflies’s existence and the characteristics of their habitat-forming environment. The research was conduct at four locations with different kinds of environmental disturbances and three replays in different periods of the season Butterfly observations were conducted by the Pollard Transect method and measuring microclimate variables, vegetation, and distance from the source of the disturbance. Determination of potential types as bioindicators is carried out with two stages of research: 1) analyzing the distribution of each type of butterfly to the environmental characteristics of Redundancy Analysis (RDA), 2) analyzing the criteria of general properties and response criteria of each type to environmental conditions. This research shows that Ypthima horsfieldii and Polyura hebe type butterflies are specialist types whose existence indicates good environmental conditions or low-disturbance environments. In contrast, Papilio demoleus is a more adaptable type, and its presence indicates impaired environmental conditions.